2010
DOI: 10.1016/j.jsv.2009.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy stability analysis of regenerative chatter in milling

Abstract: During machining, unstable self-excited vibrations known as regenerative chatter can occur, causing excessive tool wear or failure, and a poor surface finish on the machined workpiece.Consequently it is desirable to predict, and hence avoid the onset of this instability. Regenerative chatter is a function of empirical cutting coefficients, and the structural dynamics of the machine-tool system. There can be significant uncertainties in the underlying parameters, so the predicted stability limits do not necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…For monotonic problems this process may be trivial, since the maxima or minima of the inputs will lead to the maxima or minima for the output. Conversely, for non-monotonic problems this is no longer the case (Sims et al, 2010). In addition, the Standard Fuzzy Arithmetic may become problematic and lead to different results for the same problem depending on the form in which the solution procedure is applied, as can be seen in the examples gathered in (Hanss, 2002).…”
Section: Matlab -A Ubiquitous Tool For the Practical Engineermentioning
confidence: 99%
“…For monotonic problems this process may be trivial, since the maxima or minima of the inputs will lead to the maxima or minima for the output. Conversely, for non-monotonic problems this is no longer the case (Sims et al, 2010). In addition, the Standard Fuzzy Arithmetic may become problematic and lead to different results for the same problem depending on the form in which the solution procedure is applied, as can be seen in the examples gathered in (Hanss, 2002).…”
Section: Matlab -A Ubiquitous Tool For the Practical Engineermentioning
confidence: 99%
“…Kong et al [3], Kong and Yu [4], Sims et al [5] and Hamann et al [6] have used fuzzy set theory to determine the confidence ranges of the computed stability diagrams. Sims et al [5] reported that explicit fuzzy interval-based arithmetic is impractical in the analysis of machine tool vibrations. Instead, numerical methods with a specific sample of uncertain parameters have been used [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Sims et al [5] reported that explicit fuzzy interval-based arithmetic is impractical in the analysis of machine tool vibrations. Instead, numerical methods with a specific sample of uncertain parameters have been used [5,6]. Park and Qin [7] have used the edge theorem combined with the zero exclusion method in robust stability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, all these models assume that parameters of the milling process such as depth of cut, feed per tooth and cutting force are deterministic. Actually, these parameters are random in practical engineering due to uncertainty factors in real manufacturing environment, which would in turn influence the milling process (Sims et al, 2010;Graham et al, 2013;Hajdu et al, 2016). In this paper, a practical method is proposed to predict SLE in milling considering the effects of uncertain factors.…”
Section: Introductionmentioning
confidence: 99%